The Converging Discourses: Rhetorical Interplay between Islamic Thought and Arabic Literature in Nigeria - Uthman Idrees Kankawi [Corresponding Author]; AbdulGafar Olawale Fahm; Uthman Abdus Salam; Abdulhakeem Zubair (Al-Qanṭara, 2025)
Objective This study investigates the dynamic intersection between Islamic thought and Arabic literature in Nigeria, highlighting how their convergence has shaped cultural, religious, and intellectual identities within Muslim communities. It focuses on the rhetorical and thematic strategies used in Arabic literary forms to convey Islamic theological and ethical messages. Method Using a multidisciplinary, historically informed qualitative approach, the research draws from Arabic and Ajami texts, oral traditions. It includes literary and cultural analysis of works by key figures such as Shehu Usman dan Fodio, Nana Asma’u, Shaykh Adam al-Ilory, and Zakariyah Oseni. Fieldwork provided oral testimonies and insights into contemporary pedagogical practices, while archival research explored the impact of colonial and postcolonial educational policies. Results The findings reveal a rich rhetorical tradition where Arabic literature serves both as a medium for Islamic knowledge and as a tool for social commentary on governance, education, gender equity, and moral reform. Core Islamic themes like tawḥīd (divine unity), ʿadl (justice), and taqwā (piety) consistently emerge across texts. Sufi imagery and poetic forms infuse the literature with spiritual depth, while translations into local languages and oral performance styles help localise and broaden its impact. Modern educational systems and digital platforms further enhance the accessibility and relevance of this tradition. Conclusion The study concludes that this Arabic-Islamic literary tradition remains vibrant and transformative. Overcoming linguistic and institutional challenges through literacy programs, digital tools can strengthen this heritage in educational and interfaith initiatives in Nigeria.